(3EfHGA GrdZeQ HCHfGA GrdoYeQs - (3CMeO Hf Ydj Hf eMeO GdcfGfj GdYSbdGfj, CHh GdaVd, TgGH GdOjf, GHf nMnLQ,J (B852 (3g` s
(3ChdgG (B:s
(3CeG HYO gPG JYdjb LeYJ jg MhGOK GdReGf GdPi COQcJg ef ehdOi SfI (B773 (3hgd LQG , eaUdkG ai cd Sfg Yf hajGJ GdCYjGf eSJhYHkG dQhGI GdMOjK NUhUkG ef dbjJg hCLGRi s
(3BNQgG (B:s
(3SbW eQI CNQi aONd GdbG gQI eY GdQcH hgh SGde Edi Cf hcGf fSH hGddg GYde s
(3GfXQ GdbSe GdKGfi ef GdJGQjN (B587s
(3fSNI QHYIs
(3gPG GdcJGH ef MjK GdMhGOK jUdM Cf jchf Ydi JGQjN GdMGaX GHf cKjQ hef MjK GdhajGJ Cf jchf PjdkG Ydi GdhajGJ GdJi LeYgG Jbi GdOjf Hf QGaY gPG eG PcQg GdeDda ai ebOeI GdcJGHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B173s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B68 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B32 s
Keywords: (3GdJGQjNs